Analysis of the Implementation of Goods and Services Procurement through E-Catalog Version 6 in Supporting Performance-Based Budget Efficiency at the North Sulawesi Provincial Health Office - Elisabeth Marselina Mantiri; David P. E. Saerang; Jessy D. L. Warongan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the implementation of goods and services procurement through E-Catalog Version 6 in supporting performance-based budget efficiency at the North Sulawesi Provincial Health Office. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving parties responsible for planning, procurement, financial management, pharmaceutical services, and asset management. Informants were selected purposively and expanded through snowball sampling until data saturation was reached. Data were analyzed using an interactive model consisting of data reduction, data presentation, conclusion drawing, and verification. Data validity was ensured through source and technique triangulation. The findings indicate that the medicine procurement process has been implemented systematically through the collection of needs from regencies and cities, preparation of the Medicine Needs Plan, budget adjustment through the Regional Government Information System, verification using the Expenditure Standard Analysis, and transactions through the E-Catalog. The use of E-Catalog Version 6 improved access to information, price and specification comparisons, transaction transparency, and process traceability through digital negotiation and payment features. Procurement outcomes were reflected in timely delivery, relatively stable medicine availability, orderly inventory recording, and budget realization rates ranging from 96.78% to 99.59%. However, system utilization has not been fully optimized because not all types of medicine are available in the catalog. This study concludes that E-Catalog Version 6 supports performance-based budget efficiency by strengthening procurement processes, transparency, accountability, and orientation toward health service outcomes.